FAKTOR – FAKTOR YANG MEMPENGARUHI STOCK RETURN PERUSAHAAN YANG TERDAFTAR DI BEI - Virginia Ariandy Sulaiman; Maria (E-Jurnal Akuntansi TSM, 2022)
This study was conducted with the aim of providing empirical evidence related to the factors that affect stock returns. The factors used in this study are liquidity, profitability, activity, leverage, firm size, economic value added, and capital employed efficiency. The object used is data from manufacturing companies that are consistently listed on the Indonesia Stock Exchange (IDX) website during the research period from 2018 to 2020. A total of 52 company data were collected as samples with a total of 147 data that consistently passed the results of sample selection using the method. purposive sampling. The relationship between the independent variables used with stock returns was tested using multiple linear regression analysis. The results obtained from this study indicate that there is an effect of economic value added on changes in stock returns, where every increase in economic value added will have an impact on decreasing stock returns. However, liquidity, profitability, activity, leverage, firm size and capital employed efficiency have no effect on stock return.